Use of 55 PET radiotracers under approval of a Radioactive Drug Research Committee (RDRC) - Isaac M. Jackson; So Jeong Lee; Alexandra R. Sowa; Melissa E. Rodnick; Laura Bruton; Mara Clark; Sean Preshlock; Jill Rothley; Virginia E. Rogers; Leslie E. Botti; Bradford D. Henderson; Brian G. Hockley; et al. (SpringerOpen, 2020)
Abstract Background In the US, EU and elsewhere, basic clinical research studies with positron emission tomography (PET) radiotracers that are generally recognized as safe and effective (GRASE) can often be conducted under institutional approval. For example, in the United States, such research is conducted under the oversight of a Radioactive Drug Research Committee (RDRC) as long as certain requirements are met. Firstly, the research must be for basic science and cannot be intended for immediate therapeutic or diagnostic purposes, or to determine the safety and effectiveness of the PET radiotracer. Secondly, the PET radiotracer must be generally recognized as safe and effective. Specifically, the mass dose to be administered must not cause any clinically detectable pharmacological effect in humans, and the radiation dose to be administered must be the smallest dose practical to perform the study and not exceed regulatory dose limits within a 1-year period. In our experience, the main barrier to using a PET radiotracer under RDRC approval is accessing the required information about mass and radioactive dosing. Results The University of Michigan (UM) has a long history of using PET radiotracers in clinical research studies. Herein we provide dosing information for 55 radiotracers that will enable other PET Centers to use them under the approval of their own RDRC committees. Conclusions The data provided herein will streamline future RDRC approval, and facilitate further basic science investigation of 55 PET radiotracers that target functionally relevant biomarkers in high impact disease states.